Small-scale method for the determination of selected organochlorine pesticides in soil - Polese, L. [UNESP]; Minelli, E. V. [UNESP]; Jardim, E. F G [UNESP]; Ribeiro, M. L. [UNESP] (Springer Nature, 1996)
A small-scale method was developed for the simultaneous determination of γ-HCH, heptachlor, aldrin, dicofol, mirex, endosulfan I, endosulfan II and endosulfan sulphate in soil. The extraction and clean-up steps were combined into one step by transferring soil samples to chromatographic columns prepacked with neutral alumina. The pesticides elution was processed with n-hexane : dichloromethane (7:3) and the concentrated eluate was analysed using gas-liquid chromatography with electron capture detection. Analyses of the in vitro fortified samples with the selected pesticides were performed at three different levels. Mean recoveries for aldrin, γ-HCH and heptachlor, at levels of 2, 10 and 20 ng/g, ranged from 71 to 87%; for dicofol, at levels of 8, 40 and 80 ng/g, ranged from 97 to 103%; for endosulfan I and II, at levels of 5, 25 and 50 ng/g, ranged from 88 to 96%; for mirex, at levels of 6, 30 and 60 ng/g, ranged from 86 to 110%; and for endosulfan sulphate, at levels of 15, 75 and 150 ng/g, ranged from 93 to 104%. The method can be used for rapid determination of these pesticides in soil. © Springer-Verlag 1996.
Keywords: Pesticides; Soil pollution; Soils; Chlorine Organic compounds; Organochlorine compounds; Simultaneous measurement; Chemical analysis